Formação e sustentabilidade na sociedade capitalista de consumo: a gestão do material escolar em uma escola estadual de São Paulo - Souza, Ana Melicia Moraes de (2017)
This research has, as a study object, the use of school materials in a state school from São Paulo. The problem of the investigation is to know if the management of this kind of material follows the sustainability principles. It started from the hypothesis that the school materials waste and irregular use may be attached to the society consumption pattern and, also, that such materials, which is distributed by the public power, may be not being used correctly, what becomes evident through the apparent waste and punctual actions, distant from a critical view and sustainable attitudes, from the environmental point of view, by the educational agents. Seeking to understand the advances of the school materials delivery, this research proposes to carry out a legal support assessment about them, identifying controversies and contradictions that surround the resources which are available in the educational environment. The methodology includes documental analysis, focus groups with teachers and students, interview with the management team, within the scope of a case study, in a São Paulo state school. The main theoretical critical reference was the Frankfurt school Critical Theory. In the analysis result of the involved persons’ speech, we could observe that the school materials management follows the logic of the exacerbated consumption, characteristic from this capitalist society, since these materials end up not being used with sustainability principles. We have also realized that the formation is weakened, by having the theory and praxis articulation committed in its development. Finally, it is possible to affirm that there are contradictions about the school materials delivery, use and discard made by the attended community, since the formation is the main question. It is possible to say that the public policy reflects very little on the concerns about the sustainability which becomes evident in the documentary analyses. Without a users’ critical reflection, the school materials end up being wasted and discarded in an irregular way, causing damages in many spheres. The research is concluded with an intervention proposal which permits advances in the use of these materials utilized by this school community, in order to promote awareness and the viability of an educational performance based on sustainability criteria.